2021
DOI: 10.1590/2175-8239-jbn-2020-0172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of kidney transplant costs related to recovery of renal function after the procedure

Abstract: Introduction: The number of kidney transplants (KTx) is increasing in Brazil and, consequently, the costs of this procedure increase the country's health budget. We retrospectively evaluated the data of kidney transplant procedures until hospital discharge, according to kidney function recovery after the procedure. Methods: Retrospective analysis of the non-sensitized, 1st KTx from deceased donors performed between Jan/2010 to Dec/2017. Results: Out of the 1300 KTx from deceased donors performed in this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…11-18 In addition, there is evidence that patients with SGF, even if they do not require dialysis, have similar outcomes to those who require dialysis. 8,9,18,19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11-18 In addition, there is evidence that patients with SGF, even if they do not require dialysis, have similar outcomes to those who require dialysis. 8,9,18,19…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] DGF is associated with a higher occurrence of acute rejection, reduced graft survival, and increased hospital length of stay and costs. [11][12][13][14][15][16][17][18] In addition, there is evidence that patients with SGF, even if they do not require dialysis, have similar outcomes to those who require dialysis. 8,9,18,19 There are models with the objective of identifying the risk of patients who developed DGF after KTx, built using classical statistics, most of which use risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a well-designed study conducted at HC-USP, Quinino et al (2021) 7 compared the costs of kidney transplants with deceased donor in recipients with rapid (Group 1) or slow creatinine decrease without the need for dialysis (Group 2) and with the need for dialysis in the first week (Group 3). The authors demonstrated that the costs were significantly higher in groups 2 (36%) and 3 (166%) when compared with group 1.…”
mentioning
confidence: 99%
“…The authors demonstrated that the costs were significantly higher in groups 2 (36%) and 3 (166%) when compared with group 1. Based on these results, they suggest asking health authorities to reimburse kidney transplants in non-sensitized recipients with different values for these three groups 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation